EFL Studentsâ Responses on The Implementation of Extensive Reading Program to Build Love of Reading in English - Iftanti, Erna; Shofiya, Arina (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
People agree that reading is essential skill to get any knowledge in order to get the success of life either academically or socially. Reading needs to be embedded and nurtured because it is not a born skill. Still, the fact shows that EFL students in Indonesian context have not established good habits in reading English, as also experienced by EFL students in IAIN Tulungagung who are also categorized as reluctant readers due to their lack of vocabulary knowledge and number. Many studies on Extensive Reading (ER) indicate its positive impact on nurturing good habits of EFL reading in English. Accordingly implementing Extensive Reading Program to help them build love of reading is necessary. This article is then intended to dig up their responses on the implementation of ER program to the establishment of their love of reading. This research objective was achieved by distributing Reading Log during implementing Guided Extensive Reading Program (GERPro), distributing Questionnaire, and conducting interview to those involved in this ER program. The result of this research reveals that the EFL students joining this ER program claim that for those who do not establish good habits in reading English, ER proved to be able to embed their awareness of love of reading in English, and for those who already built reading love in their mother tongue-Indonesian language, their reading love in both Indonesian language and English gets increased. In addition, this GERPro contributes to the establishment of EFL studentsâ love of online reading. In short, this research result can be pedagogically implemented by EFL teachers who would like to help their students nurturing good reading habits in English. However, for those who are moody, this GERPro does not work well. Consequently, the next researcher needs to conduct a research on how to work with moody EFL students so that their reading habits can be well established.